1999
DOI: 10.1161/01.atv.19.10.2517
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin-Induced Activation of the Coagulation Cascade in Humans

Abstract: Abstract-During Gram-negative septic shock, lipopolysaccharide (LPS, endotoxin) induces tissue factor (TF) expression.TF expression is mediated by nuclear factor B and amplified by activated platelets. TF forms a highly procoagulant complex with activated coagulation factor VII (FVIIa). Hence, we hypothesized that aspirin, which inhibits LPS-induced, nuclear factor B-dependent TF expression in vitro and platelet activation in vivo, may suppress LPS-induced coagulation in humans. Therefore, we studied the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 35 publications
4
43
2
Order By: Relevance
“…In accordance with our own previous findings, 18 TFpositive monocytes doubled after LPS infusion in the placebo group. The clinical relevance of our finding is supported by a report that high tissue thromboplastin activity on monocytes predicted adverse outcome in patients with Neisseria meningitidis infection.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In accordance with our own previous findings, 18 TFpositive monocytes doubled after LPS infusion in the placebo group. The clinical relevance of our finding is supported by a report that high tissue thromboplastin activity on monocytes predicted adverse outcome in patients with Neisseria meningitidis infection.…”
Section: Discussionsupporting
confidence: 93%
“…23 Thus, we confirm our previous finding that TpP levels increase during endotoxemia. 18 We also showed that UFH and LMWH equally blunted the TpP increase after LPS (Figure 2). In contrast, using a chromogenic assay based on fibrin-mediated conversion of plasminogen to plasmin, 22 we found no increase in any study subject.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…[15][16][17] In particular, an increase in TF-expressing circulating monocytes has been documented in various conditions, including human lowdose endotoxemia, venous thrombosis accompanying different diseases and disseminated intravascular coagulation (DIC), especially sepsis-associated DIC. [27][28][29][30] In these conditions, the number of blood TF-positive monocytes, as assessed by flow cytometry, was reported to range between 5-60%, the highest values being present in septic patients with DIC. Therefore, an important question to be addressed is whether fibrinolysis can be inhibited by a concentration of TF-expressing cells comparable to that attainable in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, both Lpp and LPS activate the complement cascade, coagulation cascade, and other inflammatory mediators (24)(25)(26)(27). In addition, Lpp purified from Y. enterocolitica synergizes with its LPS to induce production of proinflammatory cytokines in vitro and in vivo, leading to septic shock (28).…”
mentioning
confidence: 99%